Factor Analysis of Demand for Kaligua Tourism in Brebes Regency: A Case Study Using Primary Data - Sarah Dien Hawa; Ahmad Syauqi; Rolisnawati Rolisnawati; Haydar Za'im Akbar (Trunojoyo University of Madura, 2023)
Based on BPS data, Kaligua tourism experienced a decrease in visitors in 2020 of 68,110 people, down to 64,325 in 2021. And it will drop again in 2022 to 51,587. This indicates a decrease in income for Kaligua tourism objects even though this sector is very important because it has a role in the economy. Against the backdrop of the current problems, it appears that the tourism sector plays a very important role in economic growth, and the growth of new tourist destinations has led to increasingly fierce competition between tourist sites to attract tourists to visit. On the other hand, services in tourism management in terms of serving tourists are not yet good. The purpose of this research is to develop a strategy that can increase the number of tourist visits in Kaligua tourism. Kaligua Tourism continues to experience a decline in visitors from 2020 to 2022, so research is needed to formulate the right strategy to increase visitors to Kali Cave tourism. This research was conducted to determine the effect of penetration pricing and consumer motivation on the decision to visit Kaligua tourism. Data were obtained through interviews. 97 Respondents who have already visited Kaligua tourism will be asked to fill out a questionnaire, and the results will be tested through smart PLS. It is hoped that this research will be able to become the basis and reference for Kaligua tourism in determining the right strategy to increase Kaligua tourism visitors.